Role of Mucobuccal Sulci in Determination of Occlusal Vertical Dimension in Dentate Subjects. - Khezran Qamar, Syed Hammad Azeem Rizvi, Aman Mansoor, Tayyaba Hamid, Warda Amjad, Kanzah Shah Nawaz, Sajid Naeem (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To find out the distance between the mucobuccal sulci of maxillary and mandibular arches and the cusp tips of posterior teeth and evaluate the occlusal vertical dimension in dentate subjects. Study Design:Cross sectional observational study. Place and duration: Prosthodontic department of Lahore Medical and Dental College, Lahore, from 2nd September 2022 till 2nd December 2022. Methodology: A total of 45 dentate subjects including 20 males and 25 females were selected. Alginate impressions (irreversible hydrocolloid) of both arches were taken in stock trays. Impressions were poured in hard plaster and stone casts were fabricated. Digital vernier caliper with accuracy of 0.01mm was used for recording the distance from the depth of mucobuccal sulci of both arches to the cusp tips of all posterior teeth of the respective arches. The distance from maxillary mucobuccal sulcus to the mandibular mucobuccal sulcus in maximum intercuspation was also calculated. Result: The distances measured from the maxillary mucobuccal sulcus to the buccal cusp tips of maxillary first premolar, second premolar and first molar were found to be 16.86mm; 15.94mm, and 15.45mmrespectively. The distances measured from the mandibular mucobuccal sulcus to the buccal cusp tips of mandibular first premolar, second premolar and first molar were 17.02mm, 15.14mm and 14.26mmrespectively. The mean distance recorded from the depth of maxillary and mandibular sulci in maximum intercuspation positions showed shortest distance at first molar areai.e.; 26.88mmas compared to the distance found in first premolar 35.22mm and second premolar 35.63mmareas. Conclusion: The mean distances recordedbetween maxillary and mandibular sulci in intercuspation position were 35.22mm, 35.63mm and 26.88mm respectively. These values may be helpful in determination of occlusal vertical dimension by selecting appropriate teeth and shaping occlusal rims while fabricating complete dentures Keywords: Dentate, Dental arch, Mucobuccal sulcus, Maxilla, Mandible, Occlusal vertical dimension, Posterior teeth.